Complementary feeding in infants born prematurely - Menezes,Larissa Vieira Pinto (2018)
ABSTRACT Purpose To investigate if there is difficulty in introducing complementary feeding in premature infants. Methods This is an exploratory, cross-sectional study performed in premature infants between six and twenty-four months of gestationally corrected age, using complementary feeding. Thirty-eight infants born prematurely were included. The feeding difficulties presented by the infants were investigated through an objective question followed by the application of a food behavior checklist for the last month. The children's clinical variables were investigated through a medical record review. An interview was conducted with those responsible for the child to identify the sociodemographic aspects and the type of breastfeeding before the corrected six months of age. Results Asked about the general perception, 50% of parents answered that their children did not present feeding difficulties in the last month. However, when a checklist was applied, 73.7% of the parents reported that their children had at least one defensive behavior at mealtime. Refusal to open their mouths (42.1%), food selectivity (28.9%), and feeding refusal (26.3%) were the most frequent defensive behaviors. The food refusal item (44.4%) had a greater association with formula feeding (p = 0.033). Conclusion The present study showed an association between the type of breastfeeding and the difficulties in complementary feeding, especially in premature infants with formula feeding, presenting food refusal during meals. We found the presence of different types of defensive behaviors at mealtime in the majority of premature infants investigated.